Numerical simulation of pore structure and heat transfer behavior in aerated concrete. (18th January 2023) - Zhao, Zhiguang; Qu, Xiaoling; Pang, Jun; Yang, Xingshuo; Wen, Haoxiang; Yu, Chaocheng; Chen, Changqing; Tian, Changan; Li, Zaibo; Zhao, Sanyin
Highlights: Aerated concretes with densities from 500 kg/m 3 to 1100 kg/m 3 were prepared. The pore structure of aerated concrete was analyzed by image analysis method. An idea of "random distribution" was developed to reconstruct the pore structure of aerated concrete. The effective thermal conductivity of aerated concrete was numerical calculated. Abstract: The pore structure of porous concrete is randomly formed, which brings thorny obstacle to accurately predict its thermal performance. In this study, a numerical approach was proposed for the simulation of pore structure and heat transfer behavior in aerated concrete. According to the porosity ( ε ) and log-normal pore size distribution parameters ( μ, σ ), an idea of "random distribution" was developed to reconstruct the pore structure via computer modeling, and also an overlap ratio ( δ ) was defined and adopted to generate a structure closer to reality. In parallel with this, a Finite Volume Model (FVM) was established to solve the energy control equation, and thus the effective thermal conductivities (ETCs) were numerically calculated. The calibrated and validated FVM model was also used to systematically study the effects of air-void content, air-void distribution and structural parameters, including pore size and porosity on the heat transfer behavior of aerated concrete. The numerical results show that the ETCs tend to slightly decrease with the increase of overlap ratio ( δ ), pore size ( μ ) and distribution ( σ ) due to an increased degree of consolidation between pores, which leads to the solid phase easily blocked by the connected pores so that the optimal heat transfer path through the solid phase conduction is blocked. Further, the comparisons of predictions of ETCs with the experimental data and other existing models indicate that the numerical predictions agree well with the experimental data, and the experimental and simulated values of the ETCs are intermediate between the Maxwell-Eucken 1 and Effective Medium Percolation Theory (EMPT) models.